IMPROVING COGNITIVE LEVEL OF STUDENTS IN EFL SMARTWATCH SUPPORTED LEARNING ACTIVITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Mobile technology is a useful tool to assist English as a Foreign Language (EFL) learning because it can help students produce language input and output (Shadiev, Hwang & Huang, 2017). Mobility of this technology enables so-called “seamless learning” in which learning experiences are smoothly connected inside and outside the classroom (Looi, Seow, Zhang, So, Chen, & Wong, 2010). One type of mobile technology are wearable devices, e.g. smart-watches (Shadiev & Yang, 2020). Smart-watches incorporate computing functions and various sensors (Bower & Sturman, 2015). For example, sensors of smart-watches can continuously measure, record, and display different physiological information of a learner (Sawaya, 2015). Smart-watches also feature such functions as texting, recording, communicating, positioning, and monitoring (Shadiev et al., 2018). In a language learning environment, learners may use a virtual keyboard or built-in microphone to create textual or verbal content and send it to other learners for peer review and comparison. Smartwatch sensors can easily measure a learner’s location when they learn in the real world to provide contextually related learning content. Smartwatches can also monitor learners’ physiological states and notify the instructor to intervene if a learner is anxious or feels discouraged.